Relationship between comorbid pathology and tumor progression. Morphological portrayal of internal organs in modeling the growth of Guerin's carcinoma under diabetic conditions - Shikhlyarova, Alla I; Kit, Oleg I; Frantsiyants, Elena M; Kaplieva, Irina V; Zhukova, Galina V; Neskubina, Irina V; Trepitaki, Lidia K; Przhedetskiy, Yuriy V; Pozdnyakova, Viktoria V; Kozel, Yulia Yu; Atmachidi, Dmitry P; Vereskunova, Alexandra A; et al. (Cardiometry, 2022)
Topicality. An increase in the incidence of malignant tumors progressing against the background of various comorbid pathologies determines the need to study the mutual influence of pathological processes using experimental modeling. Such models, for example, can reproduce the tumor growth modified by the comorbid condition of diabetes mellitus, the incidence rate of which is now increasing exponentially. In this case, a clear demonstration of changes in the structure of organs outside the zone of the primary tumor node, using data on the direct growth of the tumor and the content of diabetes markers therein and in the perifocal zone, can serve as an evidence-based argument for the implementation of the mechanism of modified tumor progression. The aim of our research work is to assess the state of the histological structure of some internal organs (the kidneys, the ovaries, the peritoneum) when modeling the main pathological process in animals, the growth of Guerin's carcinoma, against the background of a comorbid state of experimental diabetes. Materials and methods. We used 32 outbred male and female rats weighing 180-220 g to reproduce the model of experimental diabetes by a single intraperitoneal injection of alloxan at a dosage of 150 mg/kg of body weight. One week after the production of persistent hyperglycemia in the range of 25.4±1.2 mmol/l, the animals were transplanted with Guerin's carcinoma subcutaneously in the region of the right shoulder blade. Upon expiration of 2 weeks, the animals were decapitated, and the harvested organs were prepared according to the practice stages of morphological preparation for staining sections with hematoxylin-eosin, followed by morphological examination of the structure with the use of the Leica DM LS2 microscope with the Olympus optical. C-5050 Zoom video camera and the Morfotest software. Photographing was carried out with magnification x10, x40, x100. Results. Our study of the morphological portrayal of the ovary, the kidney, the visceral and parietal peritoneum bears witness to the identity of the changes, consisting in a total metastatic lesion and abnormal transformation of the normal structure of all the studied organs only in the female rats, when modeling the comorbid state of diabetes mellitus. At the same time, the aggressive nature of the tumor progression was manifested in the blood filling of the vessels and hemorrhage, followed by the release of tumor cells, their settlement, the enhanced proliferation, the formation of strands and compaction of cell aggregations throughout the volume of the organ. Some gender specific features of the tumor progression were noted, which were found in the female rats along the path of active metastasizing in case of small primary tumors, and in the male rats along the path of stimulating the growth of the primary focus without metastasizing. It was revealed that these differences are associated with different degrees of saturation of the tumor and perifocal zone with glucose, and they are determined by the state of the insulin/insulin-like growth factor (IGF) axis. Conclusion. Morphological examination of the organs affected by metastatic Guerin's carcinoma in the female rats with diabetes mellitus makes it possible to detect not only the synergy of both pathological processes, but also a powerful pro-oncogenic effect of the comorbid state of diabetes in the implementation of the tumor growth program.